Estudio de pre factibilidad para la creación de una microempresa para la producción y comercialización de muebles de madera en la cooperativa Cisne 2, parroquia Febres Cordero, cantón Guayaquil, provincia del Guayas - Garaicoa Galán, Sergio Alejandro (2015)
This research focuses on the feasibility study for the creation of a small business for the production and marketing of wooden furniture in the Cooperative Swan 2 parish Febres Cordero, Canton Guayaquil, Guayas Province, because it is an economic sector potential growth and importance in the study area as are furniture workshops category wood, to observe opportunities established in the administrative and finance because it is a zone of medium high socioeconomic levels (B), typical medium (C +) and means Low (C-) with susceptibility to job security and high informal employment, so that the proposal opportunities in these businesses improve their administrative and financial quality opting for current opportunities of the Ecuadorian State against the undertaking shown the promulgation of Good Living and the change of the productive matrix. The field methodology was applied to ten shop owners in the sector concerned. Gaps in research on the management of costs and expenses, the knowledge of their profitability and compliance with social security obligations to its employees are observed what has caused these do not have higher profit margins in relation to produced………